2011
DOI: 10.1002/mrm.22702
|View full text |Cite
|
Sign up to set email alerts
|

19F MRI detection of acute allograft rejection with in vivo perfluorocarbon labeling of immune cells

Abstract: Current diagnosis of organ rejection following transplantation relies on tissue biopsy, which is not ideal due to sampling limitations and risks associated with the invasive procedure.We have previously shown that cellular magnetic resonance imaging (MRI) of iron‐oxide labeled immune‐cell infiltration can provide a noninvasive measure of rejection status by detecting areas of hypointensity on T 2*‐weighted images. In this study, we tested the feasibility of using a fluorine‐based cellular tracer agent to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 21 publications
(39 reference statements)
3
89
0
Order By: Relevance
“…In a model of lipopolysaccharide-induced pneumonia 14 and in inflammation after cardiac and cerebral ischemia, 17 PFC was detected predominantly in the monocyte/ macrophage and dendritic cell fractions and to a lesser extent in neutrophils, whereas T cells did not incorporate the PFC. Thus, these and other data 15,25 are well in line with our current findings in the EAM model.…”
Section: Confirmation Of Infiltrating Inflammatory Cells As Source Ofsupporting
confidence: 93%
See 1 more Smart Citation
“…In a model of lipopolysaccharide-induced pneumonia 14 and in inflammation after cardiac and cerebral ischemia, 17 PFC was detected predominantly in the monocyte/ macrophage and dendritic cell fractions and to a lesser extent in neutrophils, whereas T cells did not incorporate the PFC. Thus, these and other data 15,25 are well in line with our current findings in the EAM model.…”
Section: Confirmation Of Infiltrating Inflammatory Cells As Source Ofsupporting
confidence: 93%
“…11 Finally, the 19 F signal can be fused with conventional 1 H images for anatomic coregistration. 12 As demonstrated by several groups, 13 19 F MRI is able to detect macrophages after intravenous injection of perfluorocarbons (PFC) emulsions in several disease processes, such as pneumonia, 14 heterotopic acute cardiac allograft rejection in rat and in mouse models, 15,16 and in healing after myocardial infarction in mice. 17 The goal of the current study was, therefore, to characterize the performance of 19 F-CMR for the specific detection of inflammatory cells in a mouse model of CD4 + T cell-mediated experimental autoimmune myocarditis (EAM).…”
Section: Circ Cardiovasc Imagingmentioning
confidence: 99%
“…Overall, the vast majority of studies that perform cell tracking with 19 F MRI have employed spin echo sequences. [16][17][18][19][37][38][39][40] Using the 3D bSSFP sequence, we injected and detected 1.5×10 6 Cell Sense-labeled hMSC in vivo on day 0 using a spatial resolution of 2 mm 3 (2 µL). If we assume that on day 0 all of the injected cells are present and evenly distributed, then we detected 30,000 cells per voxel.…”
Section: Cell Detection With Bssfpmentioning
confidence: 99%
“…Moreover, perfluorocarbon liquids are chemically and biologically inert, and no toxicity has ever been reported using 19 F-labeled cells, 23 even at large doses. To date, investigators have successfully used this approach to track murine macrophages, 24 19 F-MRI without apparent toxicity. 34 However, NK cells have been challenging to label using this approach 35 and data is lacking on NK cell trafficking even though they are being infused in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…14 The same group has subsequently employed 19 F-MRI to track and quantify: autoreactive mouse T cells, 27 antigen specific T cells, 28 monocyte and macrophages in two rat models of renal and cardiac allograft rejection, 24 and PFPE-labeled human primary DCs in immunodeficient mice. 25,26 Other investigators have also reported on the ability to ex vivo label other potential cell therapies with 19 F, including murine 30 and human neural stem cells, 31 human CD34 C hematopoietic stem cells (HSCs) and mouse bone marrow derived HSCs as well as murine 32 and human 33 19 F-MRI without apparent toxicity.…”
mentioning
confidence: 99%